1992
DOI: 10.1073/pnas.89.8.3320
|View full text |Cite
|
Sign up to set email alerts
|

Differential development of progenitor activity for three B-cell lineages.

Abstract: Cell-transfer studies presented here distinguish three murine B cell lineages: conventional B cells, which develop late and are continually replenished from progenitors in adult bone marrow; Ly-l B cells (B-la), which develop early and maintain their numbers by self-replenishment; and Ly-1 B "sister" (B-lb) cells, which share many of the properties of Ly-1 B cells, including self-replenishment and feedback regulation of development but can also readily develop from progenitors in adult bone marrow. The sequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
207
8
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 275 publications
(234 citation statements)
references
References 34 publications
(35 reference statements)
18
207
8
1
Order By: Relevance
“…Our results support the concept of (at least) two developmentally and functionally distinct B cell lineages within the immune system (10,(30)(31)(32): one generated during fetal life and one in the adulthood which begins to emerge after birth. Developmentally, it has been shown that embryonic (33), fetal omentum (34), and fetal liver (9, 35) B cell progenitors preferentially give rise to B-la (CD5 +) B cells.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Our results support the concept of (at least) two developmentally and functionally distinct B cell lineages within the immune system (10,(30)(31)(32): one generated during fetal life and one in the adulthood which begins to emerge after birth. Developmentally, it has been shown that embryonic (33), fetal omentum (34), and fetal liver (9, 35) B cell progenitors preferentially give rise to B-la (CD5 +) B cells.…”
Section: Discussionsupporting
confidence: 76%
“…Developmentally, it has been shown that embryonic (33), fetal omentum (34), and fetal liver (9, 35) B cell progenitors preferentially give rise to B-la (CD5 +) B cells. Given our earlier studies (10) and those of Hardy and Hayakawa (9), it is reasonable to assume that the B-la (and possibly B-lb) lineage(s) are a part of what we have defined here as the FT developmental pathway. As expected, sorted I-A-pre-B cells from young spleens can give rise to CD5 + B ceils in FLST2 cultures (Lain, K.-P., and A. M. Stall, manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, over time, peritoneal B-2 cells acquired characteristics of B-1b, not B-1a, B cells. Previous work has shown that B-1b cells can develop from bone marrow progenitors in the adult, whereas B-1a cells do not or do so at a vanishingly small rate [33]. The apparent transition of peritoneal B-2 cells toward a B-1b-like phenotype is consistent with the derivation of B-1b cells from the bone marrow.…”
Section: Discussionsupporting
confidence: 74%
“…To separate B cell subsets to B-1 and B-2 cells (17,19), lymphocytes from different tissues were incubated with FITC-conjugated anti-IgD (PharMingen, 11-26c.2a) and PE-conjugated anti-IgM (IgH-6 b ; PharMingen, AF6-78) for the IL-15-induced B cell-proliferation assay. FITC-conjugated anti-IgA (PharMingen, R5-140), PE-conjugated anti-CD45R/B220 (PharMingen, RA3-6B2), and biotinylated anti-IgM (PharMingen, AF6-78) followed by streptavidin-conjugated PerCP (Becton Dickinson, Sunnyvale, CA) were used for the separation of sIgM ϩ sIgA Ϫ or sIgA ϩ B-1 and B-2 cells for the analysis of IL-15R and C␣ expressions and IgA production (14, 16, 17, 28 -30).…”
Section: Analysis and Purification Of B Cell Subsets By Flow Cytometrymentioning
confidence: 99%